2017
DOI: 10.1007/s12272-016-0875-9
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide attenuates the level of Aβ1–42 via enhancing leptin signaling in cellular and APP/PS1 transgenic mice

Abstract: An large body of evidence indicates that leptin has protective role against Alzheimer's disease, where it reduces β-amyloid (Aβ) production in both cell culture and animal models. Our previous studies revealed that geniposide could attenuate the production of Aβ and antagonize the neurotoxicity of Aβ in neurons. However, the mechanism that underlies these effects remains to be clarified. To investigate whether leptin signaling is involved in regulating the production of Aβ by geniposide, we treated primary neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…In animal experiments, GP was diluted with DMSO to different concentrations of 25, 50, and 100 mg/kg (Cai et al, 2015); meanwhile, a stock solution at the concentration of 10 µM (Liu et al, 2017) was used and stored at −80 • C.…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal experiments, GP was diluted with DMSO to different concentrations of 25, 50, and 100 mg/kg (Cai et al, 2015); meanwhile, a stock solution at the concentration of 10 µM (Liu et al, 2017) was used and stored at −80 • C.…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
“…The CUMS-induced neurons were separately infected with the lentivirus of oe-NC, sh-NC, oe-Fezf1, sh-Fezf1, oe-Six3os1, inhibitor-NC, mimic-NC, miR-511-3p mimic and miR-511-3p inhibitor or in combination for 48 h. Other CUMS-induced neurons were firstly incubated with 10 µM GP for 24 h (Liu et al, 2017) and then separately infected with the lentivirus of sh-NC, sh-Fezf1, sh-Six3os1, mimic-NC, miR-511-3p mimic, miR-511-3p inhibitor, inhibitor-NC, oe-NC and oe-Fezf1 or in combination for 48 h. All lentiviruses were purchased from Shanghai Sangon Biotechnology Co. Ltd. (Shanghai, China), and the primer sequences and plasmids construction were conducted by Shanghai Sangon Biotechnology Co. Ltd. (Shanghai, China). Experiments were performed according to operation instructions.…”
Section: Cell Treatmentmentioning
confidence: 99%
“…As for the protective mechanism, the iridoid glycoside could induce the phosphorylation of Janus kinase 2 (JAK2) in addition to the signal transducers and activators of transcription 3 (STAT3). Furthermore, this glycoside can regulate the expression level of α- and β-secretase, which may be mediated with leptin signaling [ 170 ]. Furthermore, Aβ accumulation and cholinergic defects are considered to be related with learning and memory impairments.…”
Section: Pharmacologymentioning
confidence: 99%
“…The vast arrays of neuroprotective effects of iridoids and some monoterpenes are shown in Table 1 [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The Aβ formation, aggregation and function have been the major target areas of AD for in vitro experiments.…”
Section: Therapeutic Potential For Alzheimer’s Diseasementioning
confidence: 99%
“…By using primary cortical neurons in a culture media, Zhang et al [ 39 ] have demonstrated that geniposide enhance the phosphorylation of peroxisome proliferator-activated receptor γ (PPARγ). The effect of geniposide in the activation of the IDE promoter was also shown to be mediated via the glucagon-like peptide-1 (GLP-1) receptor while other pathways confirmed to be involved by inhibitor studies (see Table 1 ) where phosphatidyl inositol 3-kinase, PI3K, proto-oncogene tyrosine-protein kinase Src (c-Src), PPARγ, protein kinase A (PKA) and epidermal growth factor receptor (EGFR) [ 39 , 40 ]. Furthermore, in the SH-SY5Y cells, geniposide has been shown to ameliorate the cytotoxicity of Aβ along with its oligomer assembly and cytotoxicity [ 41 ].…”
Section: Therapeutic Potential For Alzheimer’s Diseasementioning
confidence: 99%